Development of a low background liquid scintillation counter for a shallow underground laboratory. (November 2015) - Erchinger, J.L.; Aalseth, C.E.; Bernacki, B.E.; Douglas, M.; Fuller, E.S.; Keillor, M.E.; Morley, S.M.; Mullen, C.A.; Orrell, J.L.; Panisko, M.E.; Warren, G.A.; Williams, R.O.; et al.
Abstract: Pacific Northwest National Laboratory has recently opened a shallow underground laboratory intended for measurement of low-concentration levels of radioactive isotopes in samples collected from the environment. The development of a low-background liquid scintillation counter is currently underway to further augment the measurement capabilities within this underground laboratory. Liquid scintillation counting is especially useful for measuring charged particle (e.g., β and α ) emitting isotopes with no (or very weak) gamma-ray yields. The combination of high-efficiency detection of charged particle emission in a liquid scintillation cocktail coupled with the low-background environment of an appropriately designed shield located in a clean underground laboratory provides the opportunity for increased-sensitivity measurements of a range of isotopes. To take advantage of the 35 m-water-equivalent overburden of the underground laboratory, a series of simulations have evaluated the scintillation counter's shield design requirements to assess the possible background rate achievable. This report presents the design and background evaluation for a shallow underground, low background liquid scintillation counter design for sample measurements. Abstract : Highlights: Graded-shielding can produce an ultra-low-background liquid scintillation counter. Location in a shallow underground cleanroom further enhances background reduction. A novel light collection design and selected low background materials are utilized. The background is predicted to be 10–100 times below typical commercial systems. Simulations tentatively predict a background rate of order 10 counts per day.